SINTESIS DAN KARAKTERISASI MATERIAL FOTOKATALIS Na2Ti6O13 MENGGUNAKAN METODE HIDROTERMAL - Cukri Rahma (Jurnal Optimalisasi, 2017)
hydrotermal method. Hydrotermal method is environmentally frendly way. This matter becaused hydrothermal method is using materials that are safe for life. Sodium hexa titanate is a semiconductor matterial that is widely used in various fields, such as is used as a photocatalyst material. From the characterization results, Na2Ti6O13 with size of 48.44 nm, and energy gap of 3.40 eV has been prepared. Na2Ti6O13 has a monoclinic crystal system with lattice parameters of a = 15.210 Å, b = 3.744 Å, c = 9.165 Å, and β = 99.050o. Photocatalyst activity was tested under UV light irradiation for 3 hours. Degradation of methylene blue (MB) by Na2Ti6O13 is found to be at 51%.Keywords: Photocatalyst, Na2Ti6O13, Degradation methylene blue